Perbandingan Metode Ekstraksi Konvensional, Pengepresan, Dan Enzimatis Terhadap Kualitas Minyak Buah Merah (Pandanus conoidues) - Yikwa , Noflin; Supriyanto, Supriyanto; Hidayati, Darimiyya (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Red fruit (Pandanus conoideus) is native to Papua. The fat content in red fruits varies, ranging from 11.2-30.7% (bk). The oil of red fruit comprises unsaturated fatty acids, especially oleic acid, linoleic, linoleic and palmitoleic acid, as well as various minor active components which include α-carotene, β-carotene, β-cryptosantine, α-tocopherol and phenolic acid Red fruit oil is also proven to be efficacious for health. The purpose of this study is to determine the influence of different extraction methods on the characteristics of red fruit oil. The design of this study uses a randomized design complete with the treatment of the ecclesiastical method. The extraction methods used are conventional, pressing and enzymatic. The study measured parameters such as analysis of yield, specific gravity, brightness and antioxidants. The results of the study showed that there was an influence of extraction method on the characteristics of red fruit oil. Employing the enzymatic extraction technique produced the best oil with a yield of 17.80%, a specific gravity of 0.76 g/mL, a brightness value of 20.37 and an antioxidant % of 26.05%